Exploring the dynamics of role transition of employees in family businesses through the evolutionary game theory - Zhang, Linrong; Wu, Mengyun; Li, Shiyu; Liu, Ruiwen; Zhu, Yuqing (Frontiers in Physics, 2023)
This investigation delves into the dynamic optimization of the progression from outsider to insider status within the context of family businesses. Utilizing a dynamic game model that incorporates three agents-leaders, insiders, and outsiders-it conducts a rigorous examination of the optimal pathway for the status transition of outsider employees in family businesses. The paramount objective of this study is to generate theoretical insights that may inform the optimization of human resources management and thereby bolster the overall performance of family businesses.The key findings of the research are as follows: 1. Outsider employees necessitate support from both leaders and insiders for a successful elevation in ranks. A collaborative relationship with insiders significantly enhances their performance. 2. The harmonious functioning of the workplace demands concerted efforts from all parties-leaders, insiders, and outsiders. The upward mobility of outsiders is contingent upon synergistic cooperation amongst all stakeholders. 3. A myriad of factors such as potential costs, benefits, and favoritism heavily influence the degree to which leaders endorse the upward mobility of outsiders. 4. Encouraging outsiders to move up in the ranks can instigate a sense of urgency among insiders, serving as a deterrent against complacency. This urgency can act as a catalyst for insiders to enhance their performance and mitigate the perceived threat to their own status.